Criterion and incremental validity of the emotion regulation questionnaire - Ioannidis, Christos A.; Siegling, A. B. (Frontiers in Psychology, 2015)
Although research on emotion regulation (ER) is developing, little attention has been paid to the predictive power of ER strategies beyond established constructs. The present study examined the incremental validity of the Emotion Regulation Questionnaire (ERQ; Gross & John, 2003), which measures cognitive reappraisal and expressive suppression, over and above the Big Five personality traits. It also extended the evidence for the measure’s criterion validity to yet unexamined criteria. A university student sample (N = 203) completed the ERQ, a measure of the Big Five, and relevant cognitive and emotion-laden criteria. Cognitive reappraisal predicted positive affect beyond personality, as well as experiential flexibility and constructive self-assertion beyond personality and affect. Expressive suppression explained incremental variance in negative affect beyond personality and in experiential flexibility beyond personality and general affect. No incremental effects were found for worry, social anxiety, rumination, reflection, and preventing negative emotions. Implications for the construct validity and utility of the ERQ are discussed.